2005
DOI: 10.1136/bmj.38677.559005.55
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of randomised controlled trials of gastro-oesophageal reflux interventions for chronic cough associated with gastro-oesophageal reflux

Abstract: Objective To evaluate the efficacy of treatment for gastro-oesophageal reflux disease (GORD) on chronic cough in children and adults without an underlying respiratory disease. Design Systematic review and meta-analysis. Data sources Cochrane, Medline, and Embase databases, references from review articles. Included studies Randomised controlled trials on GORD treatment for cough in children and adults without primary lung disease. Two reviewers independently selected studies and extracted paediatric and adult d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(99 citation statements)
references
References 22 publications
(49 reference statements)
0
88
0
11
Order By: Relevance
“…Além disso, a supressão ácida intensa, tal como é recomendada para a asma, não foi usada em nenhum dos estudos controlados. Contudo, 11 desses estudos usaram IBP como abordagem terapêutica, e as variáveis evolutivas usadas permitiram a inclusão em uma meta-análise 53 . Algum efeito benéfico sobre a tosse pôde ser percebido nos adultos com DRGE.…”
Section: Tosse Crônica Inespecíficaunclassified
“…Além disso, a supressão ácida intensa, tal como é recomendada para a asma, não foi usada em nenhum dos estudos controlados. Contudo, 11 desses estudos usaram IBP como abordagem terapêutica, e as variáveis evolutivas usadas permitiram a inclusão em uma meta-análise 53 . Algum efeito benéfico sobre a tosse pôde ser percebido nos adultos com DRGE.…”
Section: Tosse Crônica Inespecíficaunclassified
“…A systematic review found no conclusive support for the use of PPIs in reflux cough [54]. More recently, two randomised controlled trials confirmed little or no effect of PPIs on chronic cough when compared with placebo (placebo, as is common in the trials of cough, having quite a marked effect over baseline) [55,56].…”
Section: Cough and Refluxmentioning
confidence: 99%
“…Nevertheless, 11 of the studies had employed PPI therapy and the variables monitored allowed their inclusion in a meta-analysis. 53 A certain beneficial effect on coughing could be perceived among adults with GERD. The authors concluded that treatment for adults with nonspecific chronic coughing for 2 to 8 weeks could be considered as an empiric treatment test.…”
Section: Nonspecific Chronic Coughingmentioning
confidence: 99%